Blockchain-driven dual-channel green supply chain game model considering government subsidies - Zhang, Kejing; Xu, Yanxin (International Journal of Emerging Trends in Social Sciences, 2024)
In order to improve the performance of green supply chain and promote the adoption of blockchain, this paper establishes a dual-channel green supply chain consisting of a green manufacturer and a retailer, and builds Stackelberg game model considering different scenarios. We analyze the impact of blockchain operating costs and consumer uncertainty about the product greenness. Furthermore, we study the government subsidy for manufacturers' green costs and its impact on supply chain performance and blockchain adoption. Findings reveal that without blockchain technology, government subsidy can improve manufacturers' and retailers' profits. However, when blockchain is adopted, the subsidy effect depends on the blockchain operating costs. In case of higher blockchain operating cost, the product prices and greenness decrease as the green cost subsidies increase; In case of lower blockchain operating cost, the increase in green cost subsidies will lead to increased product prices and greenness; Green cost subsidies can raise profits and lower the blockchain adoption threshold.